Crystallization of dihydroxystearic acid (DHSA) produced from commercial grade palm oil based crude oleic acid employing isopropyl alcohol as solvent: a preliminary study - Koay, Gregory Feng Ling; Abdullah, Luqman Chuah; Yunus, Robiah; Choong, Thomas Shean Yaw; Siwayanan, Parthiban; Ahmad, Salmiah (Federation of Engineering Institutions of Islamic Countries, 2006)
In recent years, oleo-based chemicals have made its presence felt among the ever blooming personal care segment, slowly but gradually chipping into the industry once dominated by petrol-based chemicals. In particular, the industry has shown considerable interests in hydroxyl fatty acids due to their different behavior compared with ordinary fatty acids. Hydroxyl fatty acids and their derivatives are multipurpose intermediates in the synthesis of fine chemical products such as special cosmetics known as decorative cosmetics or make up products. One of the possible derivatives is known as dihydroxystearic acid (DHSA). The potential of DHSA (produced from palm oil based oleic acid via epoxidation with performic acid followed with hydrolysis of the epoxide) and its derivatives, e.g. octyl-dihydrostearate, sodium-dihydrostearate, zinc-dihydrostearate and magnesium-dihydrostearate, in the formulation of decorative cosmetics have been explored, mainly at laboratory scale. However, one aspect that was left out was the scaled-up production of purified DHSA to meet the demand of this multi-billion industry. This paper emphasizes on the purification of DHSA from its crude waxy form to its refined granular form, ideal for formulation, re-melting and transportation purposes, through solvent crystallization employing isopropyl alcohol (IPA). Gas chromatography (GC) analysis showed that crude DHSA had a purity of 69.0%. After crystallization, the purity of DHSA had increased to 92.2%. Particle size distribution (PSD) analysis showed that the crystals of refined DHSA had diameter ranging from 49 to 1783 microns.